Single versus dual antiplatelet therapy following transcatheter left atrial appendage closure. (19th May 2022) - Massalha, E; Beinart, R; Leshem, E; Nof, E; Guetta, V; Barbash, I; Sabbag, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Left atrial appendage occlusion (LAAO) had emerged as an alternative to anticoagulation in patients with non-valvular atrial fibrillation and a contraindication to long-term oral anticoagulants (OAC). LAAO implantation aims to reduce the risk of both systemic thromboembolism and the bleeding events associated with prolonged OAC. Post-procedural antithrombotic regimen varies among patients and may include antiaggregant (dual or single agents) or anticoagulation therapy in minority patients. The current study aims to compare the effectiveness and safety of post-procedural antithrombotic treatment with either dual antiplatelet therapy (DAPT) or single antiplatelet therapy (SAPT) in a real-world cohort. Methods: The cohort consisted of 205 consecutive patients who had undergone LAAO at Sheba medical center between the years 2010-2020. We prospectively evaluated baseline characteristics and periprocedural clinical, laboratory, and imaging data. All patients were followed by scheduled in-clinic visits. After excluding patients prescribed OAC following the procedure or deceased in the index procedure, the study cohort was divided into two groups according to the antithrombotic regimen following the LAAO: SAPT (35 patients) versus DAPT (151 patients). A propensity analysis via the stabilized inverse-probability-of-treatment weighting (IPTW) was applied. Results: The leading etiologies for transcatheter LAAO were previous gastrointestinal bleeding (41%) and previous intracranial bleeding (32%). The median CHADSVASC score is 5 [IQR:4-6]. Patients discharged with SAPT following LAAO were older (78±8 yrs vs.75±8 yrs), accompanied by an evident trend over the years of discharging more patients with SAPT instead of DAPT (Figure 1). No statistically significant differences were observed in other baseline characteristics, including gender, hypertension, diabetes mellitus, malignancy, chronic renal or heart failure. During two years of clinical follow-up, no differences in major adverse cardiovascular events were observed between the two groups (20% vs.19% for SAPT and DAPT, respectively). After applying an IPTW propensity analysis adjusting for several clinical and procedural relevant parameters, a K-M survival curve demonstrates no survival benefits of dual over single antiplatelet therapy (Figure 2). Conclusions: Among patients undergoing LAAO, post-procedural DAPT provides no survival benefits over single antiplatelet therapy.